An individualized diagnostic approach based on guidelines for chronic urticaria (CU). (June 2015) - Giménez‐Arnau, A.M.; Grattan, C.; Zuberbier, T.; Toubi, E.
Abstract: Chronic urticaria (CU), defined as the spontaneous or inducible appearance of hives, angioedema or both for 6 weeks or more, presents with a number of subtypes which all substantially impair patients' quality of life (QoL). International urticaria guidelines give clear recommendations on workup and treatment but the occurrence of CU with multiple causes and triggers (sometimes with more than one subtype occurring in a single patient) presents challenges for an individualized assessment by physicians. This review summarizes recent guidance on the classification, diagnosis and assessment of CU subtypes and discusses how currently available patient assessment tools and laboratory tests can be used in clinical practice as part of an individualized patient management plan.